Swallowing hydrodynamics visualization and aspiration quantification in a patient-specific pharyngolaryngeal model with varying epiglottis inversions - Amr Seifelnasr; Chen Sun; Peng Ding; Xiuhua April Si; Jinxiang Xi (Medicine in Novel Technology and Devices)
Impaired swallowing, or dysphagia, significantly affects patients' well-being and health. Nearly half of the patients with head and neck cancers experience dysphagia or aspiration following radiation therapy or surgery. However, current dysphagia management approaches are primarily symptom-based rather than etiology-specific, owing to a lack of clear understanding of aspiration mechanisms. This study aimed to understand the mechanisms of aspiration in an anatomically accurate pharyngolaryngeal model at different epiglottis angles. A biomechanical swallowing model was developed using transparent casts, and liquid flow dynamics were visualized using fluorescent dye from side and back views. Two liquids and two dispensing conditions were evaluated for their roles in aspiration. The results demonstrated distinct flow dynamics between water and a 1 ​% w/v methylcellulose aqueous solution and, to a lesser extent, between fast and slow dispensing for the same liquid. Three frequent aspiration sites were identified, including the interarytenoid notch, the cuneiform tubercular recess, and the vallecula, corresponding to aspiration mechanisms of notch overflow, recess overflow, and creeping flow, respectively. The angle of the epiglottis influenced flow dynamics in at least three ways: by facilitating gravity-assisted fluid movement, redistributing flow through the gap between the epiglottis tip and pharyngeal wall, and affecting creeping flow via the angle between the epiglottis base and hypopharynx. Slow dispensing of water to the anterior oropharynx resulted in a significantly high aspiration rate with a downward tilted epiglottis due to concurrent tubercle-recess overflow and vallecular creeping flow. The biomechanical model can serve as a testing platform for better understanding aspiration mechanisms and developing etiology-based strategies before and after treatments for head and neck cancers.